Clearance of human papillomavirus infection in patients with cervical intraepithelial neoplasia: A systemic review and meta-analysis. Issue 46 (13th November 2020) - Xiong, Ying; Cui, Liuyang; Bian, Ce; Zhao, Xia; Wang, Xiaoli
Abstract: Background: There are currently no available standard drugs treating human papillomavirus (HPV) infection, especially for patients with low-grade cervical lesion. Several therapies are explored but the results are inconclusive. The objective of this study was to evaluate the efficacy of reported non-invasive treatments in patients with HPV infection and cervical lesions by meta-analysis. Methods: A comprehensive search of prospective and randomized studies published from April 2000 to April 2020 was conducted in electronic databases. The statistical analyses of the pooled risk ratios (RRs) and the corresponding 95% confidence intervals (95% CIs) were performed using the Revman 5.2 software. Results: Twelve articles including 12 randomized controlled studies and 1 prospective controlled randomized pilot study were enrolled. Therapeutic medications included biological and herbal regimen, interferon regimen and probiotics. The meta-analysis showed the experimental treatments had a statistically significant improvement in HPV clearance rate compared with the controls (RR = 0.71, 95% CI [0.63, 0.80], P  < .00001); subgroup analyses stratified by regimen categories were consistent with results in the overall group. Treatment using biological and herbal regimen, interferon regimen or probiotics also resulted in a beneficial outcome in regression rate of cervical lesions compared with the controls (RR = 0.55, 95% CI [0.39, 0.79], P  = .001). The trend was more favorable in the probiotics than that in the biological and herbal regimen (RR 0.48 vs 0.72). Conclusion: Treatment of biological and herbal regimen, interferon regimen and probiotics benefit patients who have HPV infection and cervical lesions. Both the clearance of HPV and regression of cervical lesions are significant. More studies with less heterogeneity are needed to draw a concrete conclusion.